Alendronate versus Raloxifene for Postmenopausal Women: A Meta-Analysis of Seven Head-to-Head Randomized Controlled Trials. (5th January 2014) - Lin, Tiao; Yan, Shi-Gui; Cai, Xun-Zi; Ying, Zhi-Min; Yuan, Fu-Zhen; Zuo, Xi
Abstract : Purpose . The aim of this study was to directly compare the efficacy and the safety of the two agents for postmenopausal women. Methods/Principal Findings . Electronic databases were searched for relevant articles that met our predefined inclusion criteria. Seven randomized controlled trials (RCTs) involving 4054 women were identified and included. Although Aln was more effective than Rlx in increasing bone mineral density (BMD), no statistical differences were observed in reducing the risk of neither vertebral fractures (P = 0.45 ) nor nonvertebral fractures (P = 0.87 ) up to two-year followup. Aln reduced the risk of vasomotor (P = 0.006 ) but increased the risk of diarrhea compared to Rlx (P = 0.01 ). Our subgroup analysis further indicated the difference between Aln and Rlx in fracture risk and was not materially altered by the administration pattern, the age. The weekly strategy of Aln would further reduce the upper gastrointestinal (GI) disorders and might gain more bone mass increment at lumbar spine compared to its daily treatment. Conclusion . There was no evidence of difference of fracture risk reduction between Aln and Rlx. In addition, age did not obviously influence their relative antifracture efficacy. For Aln the weekly strategy would further reduce the upper GI disorders and gain more bone mass increment compared to the daily treatment. During clinical decision making, the patients' adherence and the related side-effects associated with both drugs should also be taken into account.